Museum Professionals in the Digital Era: Agents of Change and Innovation - Carvalho, Ana (2017)
From December 2016 to March 2017 the partners of project Mu.Sa – Museum Sector Alliance carried out a mapping of professional competences, digital and transferable, with the involvement of eighty-one experts in Europe, ranging from museum directors to policy makers, researchers, freelancers, etc. This study was conducted through interviews and focus groups (Portugal, Italy and Greece), and it aimed to ensure a balance between various different points of view. A mapping of training provisions was also carried out by means of desk research and an online survey. Within the project Mu.SA, research resulted in four emerging role – profiles: Digital Strategy Manager, Digital Collections Curator, Digital Interactive Experience Developer and Online Community Manager which were updated and revised according to the needs of museum professionals. This publication summarizes the research findings.